Trends in defect passivation technologies for perovskite-based photosensor - Park, Jun-Hee; Kim, Hong-Rae; Kang, Min-Jung; Son, Dong Hee; Pyun, Jae-Chul (한국세라믹학회, 2024)
Perovskites are semiconductor materials with the ABX3 structure, and they possess several attractive features, such as a tunable bandgap, high photoluminescence quantum yield (PLQY), charge mobility, and carrier lifetime. Hence, they are widely used in various applications, such as light-emitting devices, solar cells, and photosensors. However, the perovskite defects, including grain boundaries, vacancies, ion migration, and structural deformation, interfere with the effective performance of the perovskite-based devices. The intrinsic instability and trap states caused by the perovskite defects decrease the stability and performance of perovskite-based devices. Two methods of defect passivation are carried out to enhance the effectiveness of perovskite-based devices: (1) polymers and (2) chemical additives. Defect passivation protects the surface to increase stability and reduce trap states, thereby enhancing the performance of perovskite-based devices. This article reviews the technologies for defect passivation in perovskite-based devices. The effect of defect passivation has been analyzed using various methodologies: (1) surface analysis using atomic force microscopy (AFM) and scanning electron microscopy (SEM), (2) bandgap and charge carrier lifetime analysis using photoluminescence (PL) and time-resolved photoluminescence (TRPL) spectra, (3) the trap-state density calculations based on the I-V curve under dark conditions, and (4) comparison of the critical parameters of the perovskite-based devices. This review provides an overview of the defect passivation technologies available to enhance the stability and applicability of perovskite-based photosensors.